Organizational democracy and meaningful work: The mediating role of employees corporate social responsibility perceptions - Svendsen, Mari; Jønsson, Thomas Faurholt (Frontiers in Psychology, 2022)
Meaningful work is an important field of research, relating to both organizational outcomes and employee welfare. Organizational democracy has been theoretically proposed as an important antecedent to meaningful work. Nevertheless, this relationship is yet to be empirically explored. Thus, the objective of the current research is to explore the relationship between organizational democracy and meaningful work. We used structural equation modeling with self-reported, cross-sectional data from different nations and industries to test a mediation model in which corporate social responsibility (CSR) perceptions mediate the positive relationship between organizational democracy and meaningful work. Our findings confirmed that CSR perceptions partially mediate in the relationship between organizational democracy and meaningful work. Thus, based on our findings we can conclude that organizational democracy can play a direct role in increasing the experience of meaningful work, but also an indirect role trough the employees experience of CSR. Our findings have theoretical implications by adding to the classical theoretical literature that connect organizational democracy and meaningful work, and by disentangling the role of CSR perceptions in this relationship. Moreover, our findings have practical implications as our results give important knowledge to managers and organizational stakeholders that wish to increase the experience of meaningful work in organizations.